An improved hadoop load rebalancer - J, Geetha; Bhaskar N, Uday; Reddy P, Chenna (International Journal of Engineering and Technology, 2018)
Hadoop has taken an important space in the market as a result of quick growth of data. Load rebalancing in Hadoop is an area of major concern due to the unpredictable nature of tasks, new nodes added to cluster and node computing capacities. A load rebalancer that is efficient can help to improve the performance and reduce computation time. Load rebalancer and schedulers are used interchangeably in many cases. The main idea of this paper is to explore how load balancers / schedulers work in case of native Hadoop also included insights from some of the works, which identify and addresses the problems around schedulers and rebalancers. In this paper, an Improved Hadoop Load Re-balancer adopts a strategy to move the task to the node which has replica, which is faster and is topologically closer, which reduces the network congestion and execution time of Hadoop.Â Â